Reconfigurable Symmetric Lightweight Cryptosystem - B. Murali Krishna, M. Pravallika, Ch. Swetha, V. Tarun Kumar, Sk. Yawanth Basha (International Journal of Advanced Science and Technology, 2020)
Wireless communication system has become an imperative and ruling the world with day-to-day advancements. Secure communication channel path between cloud and remotely connecting IOT appliance and other portable wireless devices is necessity to avoid vulnerable attacks in digital world. The accelerated growth of lower-end applications such as RFID labels, remote sensors in various applications these appliances are used. Prompting a consistently expanding need for security. Preference to security calculations for asset constrained appliances the usage cost ought to be considered. Symmetric lightweight cryptosystem (SLWCS) is proposed less permutations with improved security and deliberate in reducing the power, area which transmits the data between authenticated users. SLWCSis designed on Artix-7 XC7A35T-1-CPG236 reconfigurable architecture with Verilog hardware description language (HDL) which is synthesized, simulated and implemented on Vivado.